Assesment on x-bracing system and v-bracing system of steel building / Nurul Iwani Roslan - Roslan, Nurul Iwani (Faculty of Civil Engineering, 2006)
This study focused on the comparing the lateral stiffness of several frames provided by concentrically braced frames ( inverted V bracing system and X bracing system using available softwares in the market. This study is limited to a rigid frame connection only, performing two dimensional analysis, having uniform sections and isotropic materials. At the end of this study, the results finally conclude the effectiveness of the bracing system ( inverted V bracing system and X bracing system ), lateral stiffness of the analysed frames, production of regression analysis equation to predict the displacement for specified section and range of size.